2021
DOI: 10.3389/fphar.2021.626166
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Related Receptor γ Agonist DY131 Ameliorates Lipopolysaccharide-Induced Acute Liver Injury

Abstract: Sepsis-associated liver dysfunction remains a challenge in clinical practice with high mortality and limited specific therapies. DY131 is a pharmacological agonist of the orphan receptor estrogen-related receptor (ERR) γ which plays a crucial role in regulating energy generation, oxidative metabolism, cell apoptosis, inflammatory responses, etc. However, its role in acute liver injury is unknown. In this study, we evaluated the effect of DY131 on lipopolysaccharide (LPS)-induced liver injury. Mice were pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Didymin, also known as isosakuranetin-7-O-rutinoside, is a common flavonoid found in many kinds of herbs, such as Origanum vulgare L. [ 12 ]. Didymin has been proven to be a potent antioxidant and possesses therapeutic effects on several types of tumors, such as lung cancer, breast cancer, and brain tumor [ 13 ]. In our previous study, we found that didymin could ameliorate dexamethasone-induced nonalcoholic fatty liver disease in C57BL/6J mice [ 14 ], suggesting that didymin might have the potential for the treatment of liver steatosis.…”
Section: Introductionmentioning
confidence: 99%
“…Didymin, also known as isosakuranetin-7-O-rutinoside, is a common flavonoid found in many kinds of herbs, such as Origanum vulgare L. [ 12 ]. Didymin has been proven to be a potent antioxidant and possesses therapeutic effects on several types of tumors, such as lung cancer, breast cancer, and brain tumor [ 13 ]. In our previous study, we found that didymin could ameliorate dexamethasone-induced nonalcoholic fatty liver disease in C57BL/6J mice [ 14 ], suggesting that didymin might have the potential for the treatment of liver steatosis.…”
Section: Introductionmentioning
confidence: 99%
“…LPS induces acute liver injury through inflammation and oxidative stress and is an important initiator of sepsis [ 11 , 12 ]. Previous studies have used a septic animal model induced by LPS to evaluate mechanisms and therapeutic strategies for sepsis-induced liver injury [ 13 ]. While the role of lncRNAs during liver disease has been extensively studied in humans, mice, and rats, little is currently known about their functional importance during LPS-induced hepatic injury in pigs, which are an ideal model species for studying human disease due to similar organ size and physiology [ 14 ].…”
Section: Introductionmentioning
confidence: 99%